Helena of Britain in medieval legend - Harbus, Antonina, 1968- (Suffolk, UK ; Rochester, NY : D.S. Brewer, 2002)
The first study to examine the origins, development, political exploitation and decline of the legend of St Helena, tracing its momentum and adaptive power from Anglo-Saxon England onwards.St Helena, mother of Constantine the Great and legendary finder of the True Cross, was appropriated in the middle ages as a British saint. The rise and persistence of this legend harnessed Helena's imperial and sacred status to portray her as a romance heroine, source of national pride, and a legitimising link to imperial Rome. This study is the first to examine the origins, development, political exploitation and decline of this legend, tracing its momentum and adaptive power from Anglo-Saxon England to the twentieth century. Using Latin, English, and Welsh texts, as well as church dedications and visual arts, the author examines the positive effect of the British legend on the cult of St Helena and the reasons for its wide appeal and durability in both secular and religious contexts. Two previously unpublished vitae of St Helena are included in the volume: a Middle English verse vita from the South English Legendary, and a Latin prose vita by the twelfth-century hagiographer, Jocelin of Furness. Antonina Harbus is Professor in the Department of English at Macquarie University, Sydney, Australia.
Helena in late antiquity and the early middle ages -- The Legend in Anglo-Saxon England and Francia -- Magnus Maximus and the Welsh Helena -- Popularisation in the Anglo-Latin histories and the English brut tradition -- Late medieval saints' legendaries -- The legend beyond the middle ages.
Includes bibliographical references (pages 193-210) and index.
Print version record.
JSTOR
Keywords: Helena, -- Saint, -- approximately 255-approximately 330.; Helena, -- Saint, -- approximately 255-approximately 330; Holy Cross -- Legends; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Holy Cross; Legends